Silver Nanocoating Technology in the Prevention of Prosthetic Joint Infection - Gallo, Jiri; Panacek, Ales; Prucek, Robert; Kriegova, Eva; Hradilova, Sarka; Hobza, Martin; Holinka, Martin (Materials (Basel, Switzerland), 2016)
Prosthetic joint infection (PJI) is a feared complication of total joint arthroplasty associated with increased morbidity and mortality. There is a growing body of evidence that bacterial colonization and biofilm formation are critical pathogenic events in PJI. Thus, the choice of biomaterials for implanted prostheses and their surface modifications may significantly influence the development of PJI. Currently, silver nanoparticle (AgNP) technology is receiving much interest in the field of orthopaedics for its antimicrobial properties and a strong anti-biofilm potential. The great advantage of AgNP surface modification is a minimal release of active substances into the surrounding tissue and a long period of effectiveness. As a result, a controlled release of AgNPs could ensure antibacterial protection throughout the life of the implant. Moreover, the antibacterial effect of AgNPs may be strengthened in combination with conventional antibiotics and other antimicrobial agents. Here, our main attention is devoted to general guidelines for the design of antibacterial biomaterials protected by AgNPs, its benefits, side effects and future perspectives in PJI prevention.
Keywords: anti-adhesive; silver nanoparticles; anti-biofilm; silver nanocoating; antibacterial surface treatment; biomaterial-associated infection; prosthetic joint infection